Manajemen Strategi Pengembangan Pertanian Kota (Urban Agriculture) di Kota Tangerang Selatan - Maharisi, Sodak; Maulana, Agus; Machfud (Universitas Brawijaya, Indonesia, 2014)
The Development of the agricultural sector in the South Tangerang City faces severe challenges related to the lack of resources, especially land. Urban agriculture has an important role in addressing various problems in which faced by the city. This research aimed to formulate alternative strategies of urban agricultural development in South Tangerang City. The vision and mission are formulated based on content analysis of stakeholder expectations and industry foresight, while the strategy formulation using IE matrix and use the balanced scorecard framework. Expected condition of urban agriculture development is the increased revenue of the city welfare (economic perspective). South Tangerang city government positions in developing urban agriculture located on the cell V. The best strategy is to continue to run a variety of programs and activities that have been imple mented. Strategies that can be implemented by the government are the increased intensityof the program and activities as well as creating new types of services.